Does Democracy Have a Future? - Arnold, Puyok (UNIMAS Publisher, 2023)
The book is a compilation of selected papers presented at the Third International Conference on Elections and Democracy (E & D) on April 19-20, 2017, Kuching, Sarawak with the theme "Does Democracy Have a Future?" organised by the Faculty of Social Sciences and Humanities, UNIMAS. The seven papers selected in this book merit a closer look. They were written by academics and political observers based in Indonesia, the Philippines, and Malaysia.